Myofascial Release as a Means of Injury Prevention and Movement Amplitude Recovery in Qualified Football Players - Doroshenko, Eduard; Kokareva, Svitlana; Kokarev, Borys; Nikanorov, Oleksiy; Sushko, Ruslana; Sushchenko, Lyudmyla (Physical Education Theory and Methodology, 2023)
The purpose of the study was to determine the effectiveness of MFR tools used in the training process of qualified football players. Materials and methods. The study participants were 28 football specialists of the Ukrainian Premier League football teams and 36 football players of FC “Zorya” (Luhansk). Methods used in the study included analysis, generalization and systematization of data from scientific and methodical literature and Internet, questionnaire survey, pedagogical observations, pedagogical testing of flexibility indicators, pedagogical experiment, methods of mathematical statistics. Results. The results of using MFR manual techniques in the training process of qualified football players are as follows: relaxation of chronically tense muscles, recovery of mobility and normal amplitude of motion in the joints, improvement of the elastic properties of the muscular and ligamentous structures of the musculoskeletal system of football players, optimization of hemodynamics and lymphodynamics at the microcirculatory level, optimization of general and local metabolic processes in the body, functional recovery of the musculoskeletal system of football players after excessive physical exertion and injuries, improvement of proprioception and neuromuscular control, optimization of the psychoemotional state. Conclusions. The analysis of the results of testing the flexibility of football players of FC “Zorya” (Luhansk) at the end of the first and second preparatory periods of the 2019-2020 sports season allows us to state the presence of higher indicators compared to the results of preliminary testing in the 2018-2019 sports season. According to the results of the monitoring performed by the specialists of the complex scientific group, there has been recorded an 11.11% decrease in the number of injuries related to damage to the muscular-ligamentous structures of the lower limbs and trunk of football players in FC “Zorya” (Luhansk).